Una aproximación teórica a la deserción estudiantil universitaria - Viale Tudela, Héctor Ernesto (2015)
College student dropout is one of the greatest problems faced by the higher education system. University authorities have been showing great concern because, in spite of the increase in demand for higher education, the number of students that complete their education is not as expected, demonstrating that a large number of students abandons school, mainly during the initial semesters. This generates financial problems to the universities. This paper aims to show, after a comprehensive literature review, existing models in connection with college student dropout and answer the questions to this regard